PERIPHERAL NEUROPATHIES IN PATIENTS WITH CHRONIC KIDNEY DISEASE: Peripheral neuropathy and renal failure - Stolić, Radojica; Mitrovic, Vekoslav; Mitrovic, Vladimir (Acta medicae Medianae, 2025)
Patients with chronic kidney disease often suffer from peripheral neuropathies, which have a significant impact on morbidity and mortality. Therefore, it is important to understand their pathophysiological mechanism to enable an effective management strategy for these neurological complications. This review aimed to highlight the importance of detecting clinical parameters that enable the diagnosis and early treatment of peripheral neuropathy (MRI). To achieve the goal of this review paper, we used PubMed and MEDLINE databases. The information presented in this work is gathered from the literature with the keywords peripheral neuropathy, chronic renal failure, hemodialysis, clinical picture, and treatment. At the beginning of 2024, we conducted research in the PubMed and Medline databases. Based on the established criteria for searching the literature related to peripheral neuropathy in patients with end-stage renal disease, in the last ten years, as well as some earlier works that were of interest to the issue of peripheral neuropathy, out of a total of 22 works that met the inclusion criteria, there were 8 review works, 9 original works, 4 case reports, and 1 monograph.